CT angiography in the diagnosis of cardiovascular disease: A transformation in cardiovascular CT practice. - Sun, Zhonghua; Almoudi, M.; Cao, Y. (AME Publishing Company, 2014)
Computed tomography (CT) angiography represents the most important technical development in CT imaging and it has challenged invasive angiography in the diagnostic evaluation of cardiovascular abnormalities. Over the last decades, technological evolution in CT imaging has enabled CT angiography to become a first-line imaging modality in the diagnosis of cardiovascular disease. This review provides an overview of the diagnostic applications of CT angiography in cardiovascular disease, with a focus on selected clinical challenges in some common cardiovascular abnormalities, which include abdominal aortic aneurysm, aortic dissection, pulmonary embolism and coronary artery disease. An evidence-based review is conducted to demonstrate how CT angiography has changed our approach in the diagnosis and management of cardiovascular disease. Radiation dose reduction strategies are also discussed to show how CT angiography can be performed in a low-dose protocol in the current clinical practice.